2022
DOI: 10.3390/ma15010333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nesfatin-1 on Rat Humerus Mechanical Properties under Quasi-Static and Impact Loading Conditions

Abstract: The investigations on the response of bone tissue under different loading conditions are important from clinical and engineering points of view. In this paper, the influence of nesfatin-1 administration on rat humerus mechanical properties was analyzed. The classical three-point bending and impact tests were carried out for three rat bone groups: control (SHO), the humerus of animals under the conditions of established osteopenia (OVX), and bones of rats receiving nesfatin-1 after ovariectomy (NES). The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The authors stated that for higher loading rates the bone exhibited lower fracture toughness. Similar results were obtained by Skic et al, [18], who showed that the force needed to fracture under dynamic loads was lower than the force at fracture under quasi-static conditions.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The authors stated that for higher loading rates the bone exhibited lower fracture toughness. Similar results were obtained by Skic et al, [18], who showed that the force needed to fracture under dynamic loads was lower than the force at fracture under quasi-static conditions.…”
Section: Introductionsupporting
confidence: 90%
“…The mass moment of inertia of the pendulum arm I P = 0.072 kg•m 2 allowed to obtain a constant velocity (V I ) during the impact. Before starting the test, the pendulum was set vertically, the angular displacement sensor readings were zeroed, and then the arm was defl ected by an angle of 9.15° that allowed to obtain a specifi c speed value V I = 0.5 m•s -1 [18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…COX-2, IL-6 and IL-8 in human primary chondrocytes in patients with osteoarthritis ( 30 ); it may play a role in pathogenesis or osteoarthritis, although the exact pathogenesis remains undefined ( 30 , 87 , 88 ). Pre-clinical studies have shown nesfatin-1 to be protective of bone tissue in rodents ( 31 , 32 ). Thus it was suggested that this adipokine may be used therapeutically in the management of OP ( 89 ).…”
Section: Introductionmentioning
confidence: 99%